PENINGKATAN KUALITAS LAYANAN AKADEMIK DALAM MENDUKUNG TRANSFORMASI PTKIN - Yayat Supriyadi; Encep Syarifudin; Rizal Firdaos; Sholahuddin Al Ayubi; Ilzamudin Ilzamudin; Yogi Damai Saputra (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2024)
The quality of academic services at a university is a very important factor in determining the comfort for students in taking courses in higher education, whether or not academic services will also determine the level of accreditation of the university. In some literature, it shows that higher education today has become a highly competitive market where students generally look for campuses that have quality education systems and services in supporting lectures at universities as a place of education. The extent of service innovation carried out by educational institutions in supporting the transformation that has been carried out will greatly affect the quality of students and the quality of education in Higher Education including Islamic Higher Education. This research was conducted using interview methods, surveys, statistical data analysis, and in-depth documentation studies at PTKIN, this writing can provide valuable insights into the relationship between improving the quality of academic services and the transformation of State Islamic Religious Universities (PTKIN) that has been carried out.